2014
DOI: 10.1089/dia.2014.0074
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of the Accuracy of Roche AccuChek Inform and Nova StatStrip Glucose Meters when Used on Critically Ill Patients

Abstract: The newer-generation (StatStrip) glucose meter met more stringent CLSI POCT12-A3 accuracy criteria because of reduced bias compared with the previous-generation device. Reduced glucose meter bias led to fewer insulin dosing discrepancies when the insulin dose determined from serum glucose was compared with that determined from the glucose meter value using the institutional glycemic control protocol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 18 publications
2
14
0
4
Order By: Relevance
“…Newer meter technologies may provide more accurate glucose measurement 1214 when used on critically ill patients, though studies have not specifically addressed capillary sampling or use of meters intraoperatively. One previous study 33 specifically examined glucose measurements in the OR, although few patients were under anesthesia at the time of sample collection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer meter technologies may provide more accurate glucose measurement 1214 when used on critically ill patients, though studies have not specifically addressed capillary sampling or use of meters intraoperatively. One previous study 33 specifically examined glucose measurements in the OR, although few patients were under anesthesia at the time of sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…Though newer technologies may provide more accuracy 1214 , there is still concern about the use of meters in the critically ill 15,16 . Studies have demonstrated potentially dangerous discrepancies in capillary glucose measurement in patients on vasopressor therapy 10,17 , patients in shock 18 or with poor tissue perfusion 19 , and in other critically ill patient populations 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have reported similar findings in adult patient populations. (5, 16, 17) As such, the MAUDE database entry for BGMS-2 yielded only 28 total entries, with four erroneous measurements and no adverse events or deaths since the device’s release in 2006. One of these four erroneous BGMS-2 measurements was due user error where capillary fingerstick specimens were improperly obtained in a patient with severe hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in biosensor technology have enabled the development of BGMS’s that autocorrect for these confounding factors. (5, 1618) The unique autocorrecting features of recent BGMS’s are based on the simultaneous measurement of hematocrit and oxidizing/reducing substances during the testing process—allowing these biosensors to adjust for interferences. Additionally, these autocorrecting BGMS’s incorporate modified glucose oxidase enzymes that are not susceptible to the same oxygen tension affects found in older generation devices.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing the current regulatory focus on point-of-care (POC) glucose testing in the critically ill (2,11,12 ), a recent study compared retrospective performance of glucose meters in critically ill patients by use of POC and central laboratory events drawn within 5 min of each other (13 ). Such measurements constitute coincident testing events that can be harnessed for quality assessment.…”
mentioning
confidence: 99%